Pengabdian Kepada Masyarakat Melalui Penyuluhan Jamu Sehat Kecamatan Galang Kota Batam - Suhaera Suhaera; Sri Hainil; Yunisa Friscia Yusri; Shinta Sari Dewi (Jurnal Pengabdian Ilmu Kesehatan, 2021)
Jamu, as a traditional Indonesian drink, has become a symbol of cultural richness and local wisdom inherent in ancestral heritage, reflecting the deep connection between humans and nature as well as the passing down of knowledge about medicinal plants. Local wisdom plays a central role in the use of herbal medicine, emphasizing harmony between humans and nature and Indonesia's biodiversity. In the midst of modernization, herbal medicine continues to adapt to changing times and market demands, but its traditional values are still maintained. An outreach activity about herbal medicine in Galang District involved lecturers and two students from the Mitra Bunda Health Institute as well as 100 participants from the local community, starting from preparing materials and tools for making herbal medicine, discussing materials, to morning exercises at the Rempang Cate Community Health Center, all carried out together with the community. Making herbal medicine empon-empon is done by adding enough brown sugar to get the right taste. People feel fresh benefits after consuming herbal medicine and are inspired to understand the manufacturing process more deeply.